Workplace environment effect employee' productivity at Syarikat Air Terengganu, Kuala Terengganu / Nur Haafizhah Ismail - Ismail, Nur Haafizhah (Faculty of Business and Management, 2018)
The purpose of this research was to investigate the effect of Workplace Environment toward Employees' Productivity at Syarikat Air Terengganu Sdn.Bhd., Kuala Terengganu, Terengganu. This study used simple random for sampling technique and the sample size was determined using Krejcie and Morgan (1970). Survey questionnaires were distributed to 92 respondents who worked as support staff and yield 86.96% response rate. Majority of the respondents were female, aged 31 to 40 years old and from STPM/Diploma education level. Many of them has 6-10 years of experience. The findings showed that there was a moderate relationship between Workplace Environment and Employees' Productivity (r= .485, p=0.00). Moreover, the descriptive statistics was also significant as a result for furniture (mean=3.77, SD=.386), noise (mean=3.39, SD=.826), temperature (mean=4.020, SD=.489), lighting (mean=3.85, SD=.420) and spatial arrangement (mean=3.70, SD=.598). The result also indicated there are relationship between workplace environment and employees' productivity. It is recommended that managers should improve the productivity of the employee by alert with workplace environment. Future research should study on several different types of method to gather the data. This method can road to paperless and easy the author to gather and distribute questionnaire other than time saving.